The effectiveness and complications of lrabeculectomy in Dr. Sardjilo Central General Hospital, Yogyakarta - Suhardjo, Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1987)
The effectiveness of trabeculectomy has been studied in 65 primary glaucomatous patients consisting of 30 men and 35 women. The trabeculectomy was able to control the intraocular pressure in 89% of cases and it improved visual acuity in 67.69% of cases. Based on the iridocorneal angle appearances, the cases of primary closed angle glaucoma were more frequent than those of primary open angle glaucoma. The most frequent complication found was hyphaema which occured in 23.08% of cases, but it I usually disappeared in 7 days post-operatively. Anterior uveitis was the second complication and this happened in 6.15% of cases. Other complications such as flat anterior chamber and cataract were very rare. Conjunctival fistula, bleb rupture and intraocular infection were not found here. Key Words: trabeculectomy - glaucoma - control of intraocular pressure - visual acuity improvement - hyphaemia